1993
DOI: 10.1104/pp.102.1.195
|View full text |Cite
|
Sign up to set email alerts
|

Aleurones from a Barley with Low [alpha]-Amylase Activity Become Highly Responsive to Gibberellin When Detached from the Starchy Endosperm

Abstract: The physiological and molecular bases for contrasting a-amylase phenotypes were examined in germinating seeds of two barley (Hordeum vurgare 1.) cultivars, Morex and Steptoe. Morex is a high-quality malting barley that develops high a-amylase activity soon after germination. Steptoe is a feed barley that develops only low a-amylase activity levels during this period. l h e expression of all high-and low-isoelectric point (pl) a-amylase isozymes is reduced in Steptoe. The amount of a-amylase mRNA per gram of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 35 publications
2
29
0
1
Order By: Relevance
“…This view is supported by our results showing that overexpression of VP1 in aleurone of germinating maize seeds was effective in repressing Amy-GUS (Table 2). A role of VP1 in maintaining seed dormancy is also consistent with the finding that dormancy in barley is correlated with a reduced GA inducibility of a-amylase genes in the aleurone (Schuurink et al 1992;Skadsen 1993). Hence, we suggest that VP1 plays a role in integrating the control of seed maturation, dormancy, and germination programs.…”
Section: Vpi Integrates T H E Control Of Seed Maturation and Germin Asupporting
confidence: 75%
“…This view is supported by our results showing that overexpression of VP1 in aleurone of germinating maize seeds was effective in repressing Amy-GUS (Table 2). A role of VP1 in maintaining seed dormancy is also consistent with the finding that dormancy in barley is correlated with a reduced GA inducibility of a-amylase genes in the aleurone (Schuurink et al 1992;Skadsen 1993). Hence, we suggest that VP1 plays a role in integrating the control of seed maturation, dormancy, and germination programs.…”
Section: Vpi Integrates T H E Control Of Seed Maturation and Germin Asupporting
confidence: 75%
“…Farooq et al (2006) considered that the higher the α-amylase activity the higher would be metabolic activity in seeds, which indicated the higher germination ability. Skadsen (1993) reported that higher quality malting barley showed high α-amylase activity soon after germination, whereas a poor malting quality variety showed little α-amylase activity. In this study, sand priming improved α-amylase activity and accelerated the increase of α -amylase activity during seed germination.…”
Section: Discussionmentioning
confidence: 99%
“…Ovary and anther RNAs were extracted using an RNeasy kit (QIAGEN). Seed RNAs were extracted as described (Skadsen 1993). Pericarp RNA for differential display was extracted from Morex seeds at the early dough stage of development.…”
Section: Methodsmentioning
confidence: 99%